Steamships HAMLIN, OGILVIE, AND MCCONNELL at dock in the Stikine River at Wrangell, n.d. - Nowell, Frank H., 1864-1950 (1894)
Caption on image: Nowell, 1268 On verso of image: Stickine River Boats at Wrangle, Alaska Tlingit Indian name meaning Great River, reported in 1799 as Stikine River by Capt. Rowan of the whaling ship ELIZA out of Boston. Published in 1848 on Russian charts as Ryka Stakhin or Stakin River. The present spelling of the name was adopted in 1869. (pg. 919) Notes from Donald Orth, Dictionary of Alaska Place Names: Geological Survey Professional Paper 567 (Washington: United States Government Printing Office, 1967) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number